"What if I don’t know the answer?": Fifth-grade Students’ Responses to Uncertainty in Test-Taking - Childs, Ruth A; Elgie, Susan; Brijmohan, Amanda; Yang, Jinli (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
Fifth-grade students watched a short video and then responded to multiple-choice items, including several without correct answers. Based on computer-supported stimulated recall and semi-structured interviews, we tested three common assumptions about what students are thinking when they respond to multiple-choice items in spite of being uncertain of the correct answer. We found that none of the assumptions applied to all students. For example, many of the students believed leaving items blank was unacceptable, in part because it might create the impression that they were not trying on a test. Furthermore, although most students recognized when they were uncertain, a few did not. Keywords: multiple-choice items, response processes, uncertainty, meta-memory, guessing